Reading Interests of Class VIII Students of SMP Negeri 1 Watansoppeng on Narrative Texts in Bugis Language - Putri Ayu Lestari; Syamsudduha Syamsudduha; Andi Agussalim AJ (Panrita: Jurnal Bahasa dan Sastra Daerah serta Pembelajarannya, 2021)
This research is a survey research. Surveys are used to collect correct data or information using a relatively small sample. The purpose of this study was to describe the reading interest of class VIII of SMP Negeri 1 Watansoppeng on the narrative text of Bugis language. This research was conducted on September 13 - October 11 in the odd semester of 2020/2021. The population in this study were all students of class VIII SMP Negeri 1 Watansoppeng, totaling 192 students. Sampling in this study used the Krejcie and Morgan tables. The sample in this study were 127 students of class VIII SMP Negeri 1 Watansoppeng. The data collection technique used was to provide online questionnaires via Google Form to students. Reading Interests of Class VIII Students of SMP Negeri 1 Watansoppeng towards Narrative Texts in Bugis language are in the medium category with a percentage value of 64.6% (82 students) of 127 students. This means that basically students like reading narrative text in Bugis language, but more because in the context of doing school work, not because they have reading interest in the narrative text in Bugis language